Repetitive transorbital alternating current stimulation in optic neuropathy. - Gall C; Fedorov AB; Ernst L; Borrmann A; Sabel BA (NeuroRehabilitation, 2010)
Background: Visual field defects after optic nerve damage typically show a limited capacity for spontaneous and treatment-induced recovery. Objective: Repetitive transorbital alternating current stimulation (rtACS) was applied to the damaged optic nerve to evaluate visual functions after stimulation. Methods: A 27-years-old male patient suffering left optic nerve atrophy with nearly complete loss of vision 11 years after atypical traumatic damage was treated transorbitally with biphasic 10-15 pulse trains of rtACS (10-30 Hz, < 600 μA, 30-40 min daily for 10 days) which produced phosphenes. Results: After rtACS treatment detection ability of super-threshold stimuli increased from 3.44% to 17.75% and mean perimetric threshold from 0 dB to 2.21 dB at final diagnostics. Conclusion: This improvement of vision may be due to increased neuronal synchronization, possibly involving strengthening of synaptic transmission along the central visual pathway.